Mediating Quizzes as Assessment Tool through WhatsApp Auto-response in ELT Online Class - Agus Husein As Sabiq; Muhammad Ikhsanul Fahmi (Langkawi: Journal of The Association for Arabic and English, 2020)
Although extensive studies have been conducted on the use of WhatsApp in language teaching and learning, little empirical research has been conducted to explore the use of WhatsApp modified with artificial intelligence called auto-responder as a media for assessment. To fill this void, this research aims to explore the use of WhatsApp Auto-response developed by the teacher to mediate quizzes as the assessment tool in an online English class. This research was carried out in a Vocational High School in Banyumas Regency, Indonesia, with an English teacher and his 36 students. The researchers used documentation, structured interviews, and open-ended questionnaires to collect the data. The researchers found that modifying WhatsApp with auto-responder made the online assessment more objective, accountable, transparent, easy-to-access, and easy-to-operate for both teacher and students. WhatsApp Auto-response could encourage students’ autonomous learning because they could directly know their scores and the discussion of each question. Thus, students had more interest and motivation to get a higher score. However, unstable internet connection and slow response from the application should be resolved to make it better for learning. The findings imply that supporting teaching with the technological advancements of artificial intelligence in WhatsApp can provide students with realistic self-guided learning. With WhatsApp's popularity as a learning tool nowadays, its features can be embedded with chatbots that can give many advantages as a teacher assistant, especially for facilitating assessments.